Wildfire size alters long‐term vegetation trajectories in boreal forests of eastern North America. (29th January 2017) - Remy, Cécile C.; Lavoie, Martin; Girardin, Martin P.; Hély, Christelle; Bergeron, Yves; Grondin, Pierre; Oris, France; Asselin, Hugo; Ali, Adam A.
Abstract: Aim: Wildfire activity is projected to increase under global warming in many parts of the world. Knowledge of the role of these disturbances in shaping the composition of boreal forests is needed to better anticipate their future impacts. Here, we investigate the incidence of wildfire activity (burned biomass, frequency and size) on multi‐millennia vegetation trajectories in two coniferous boreal forest regions that display different types of vegetation composition and relief. We hypothesize that this difference in vegetation results from dissimilar wildfire activity during the Holocene. Location: Conifer‐dominated boreal forests in Quebec‐Labrador, eastern North America. Methods: Fire and vegetation histories during the last 8000 years were reconstructed and compared through analyses of charcoal and pollen records extracted from nine lacustrine deposits located in two spruce‐moss forests: the western region, co‐dominated by Pinus banksiana, and the eastern region, co‐dominated by Abies balsamea . Results: Between 7000 and 2000 cal. yr bp, the western region experienced fewer fires than the eastern region, but they were larger in size. The main species adapted to fire, P. banksiana and Alnus viridis ssp. crispa, progressively co‐dominated with Picea sp.. Conversely, in the eastern region, P. banksiana and A. viridis ssp. crispa were very rare, and Picea sp. co‐dominated with non‐fire‐adapted A. balsamea and Betula sp.. Then, around 2000 cal. yr bp, fires decreased in frequency but were larger in size in the eastern region than in the western one, thus allowing densification of P. banksiana and A. viridis ssp. crispa in these landscapes. Main conclusions: In the coniferous boreal forests of eastern North America, fire size was relatively more important in determining the long‐term vegetation trajectories in comparison with fire frequency. Changes in the rate of occurrence of large‐fire episodes will have significant impacts on vegetation dynamics over the next decades under continuing warming.